2022
DOI: 10.3390/plants11212953
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Duckweed Lemna minor to Microplastics and Its Potential Use as a Bioindicator of Microplastic Pollution

Abstract: Biomonitoring has become an indispensable tool for detecting various environmental pollutants, but microplastics have been greatly neglected in this context. They are currently monitored using multistep physico-chemical methods that are time-consuming and expensive, making the search for new monitoring options of great interest. In this context, the aim of this study was to investigate the possibility of using an aquatic macrophyte as a bioindicator of microplastic pollution in freshwaters. Therefore, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…When plants were treated with pulse colloidal silver–low nutrient level co-exposure, significantly higher levels of H 2 O 2 accumulation and lipid peroxidation were measured in the treated plants, alongside the more pronounced reduction in photosynthetic pigment content in comparison to the same silver pulse treatment combined with high nutrient levels. Rozman and Kalčiková [ 26 ] found that changes in environmental conditions may influence the ability of plants to respond to the abiotic stress factor. The results of this study are in agreement with this statement; external nutrient levels had a significant effect on the L. gibba plant’s response to colloidal silver presence in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When plants were treated with pulse colloidal silver–low nutrient level co-exposure, significantly higher levels of H 2 O 2 accumulation and lipid peroxidation were measured in the treated plants, alongside the more pronounced reduction in photosynthetic pigment content in comparison to the same silver pulse treatment combined with high nutrient levels. Rozman and Kalčiková [ 26 ] found that changes in environmental conditions may influence the ability of plants to respond to the abiotic stress factor. The results of this study are in agreement with this statement; external nutrient levels had a significant effect on the L. gibba plant’s response to colloidal silver presence in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Duckweed species are suitable model plants due to their high ecological significance as a primary producer and their role in aquatic environments as a source of food and habitat for many different animals [ 24 ], as well as their high sensitivity to numerous potential pollutants [ 25 ]. Additionally, Rozman et al [ 26 ] found that external environmental conditions may affect the abiotic stress response mechanisms of treated duckweed.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement for each MPs was repeated three times and the results were expressed as the number particle size distribution. The number of particles per mass of MPs was determined as described in Rozman and Kalčíková 45 . Briefly, approximately 1–2 mg of MPs was weighted and counted under a stereo microscope (SMZ-171, Miotic, China).…”
Section: Methodsmentioning
confidence: 99%
“…fibers, cellulose particles, and wood dust was examined on the surface of duckweed, and it was found that the adherence of PE MPs was far greater than other tested particles (Rozman and Kalcǐḱova, 2022b). This can be explained by the initial interaction between duckweed and MPs, as negatively charged plant biomass attracts positively charged MPs (Kalcǐḱova, 2020).…”
Section: Figurementioning
confidence: 99%